Tsenguluso ya mushumo wa makhadzi kha mvelele ya tshivenda - Mudau, Mpfariseni Andrew (University of Limpopo (Turfloop Campus), 2012)
The mini-dissertation investigated the role played by an aunt in African Culture with special reference to Tshivenḓa. The study has discovered that an aunt played an important role in a family. Nowadays, other people are involved in the role played by makhadzi. This seems as if the community is confused about the role of makhadzi
Thesis (M.A. (African Languages)) --University of Limpopo, 2012
Keywords: Makhadzi; Venda culture; 306.850968; Personality and culture; Venda (African people) -- South Africa; Aunts